1981
DOI: 10.1104/pp.68.4.808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH, Mg2+, CO2 and Mercurials on the Circular Dichroism, Thermal Stability and Light Scattering of Ribulose 1,5-Bisphosphate Carboxylases from Alfalfa, Spinach and Tobacco

Abstract: Circular dichroism, differential scanning calorimetry and light-scattering measurements of ribulose 1,5-bisphosphate carboxylase (E.C. 4.1.1.39) from alfalfa, spinach and tobacco show: a) The conformation and thermal stability of the native carboxylases are sensitive to changes in pH and to activation of the enzyme with Mg2e and CO2. The helical content, denaturation temperature (Td) and specific enthalpy of denaturation (Aq) decreased with increase in pH. Addition of Mg2e and CO2 at pH 9 increased Td by 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our data on the C. reinhardtii RUBISCO are in good agreement with those obtained by Chen et al (1993). In the mesophilic alga, as in spinach, tobacco, and alfalfa (Tomimatsu andDonovan 1981, Eckardt andPortis 1997), RUBISCO is a remarkably stable enzyme. The ''cold'' RUBISCOs analyzed in this work present an increased thermosensitivity when compared to the C. reinhardtii enzyme.…”
Section: Resultssupporting
confidence: 89%
“…Our data on the C. reinhardtii RUBISCO are in good agreement with those obtained by Chen et al (1993). In the mesophilic alga, as in spinach, tobacco, and alfalfa (Tomimatsu andDonovan 1981, Eckardt andPortis 1997), RUBISCO is a remarkably stable enzyme. The ''cold'' RUBISCOs analyzed in this work present an increased thermosensitivity when compared to the C. reinhardtii enzyme.…”
Section: Resultssupporting
confidence: 89%
“…Activation by CO2 and metal ions with formation of a ternary complex is a property common to all rubiscos regardless of their taxonomic origin (Lorimer & Maziorko, 1983;Andrews & Lorimer, 1987). Interestingly, addition of Mg2+ and CO2 enhances the thermal stability of the hexadecameric rubisco without any effect on the subunit cooperativity (Tomimatsu & Donovan, 1981). It was also recently found that pretreatment of the enzyme with Mg2+ and CO2 prevents the inactivation that is known to occur in spinach rubisco upon storage of dilute solutions in the cold (Heuer & Portis, 1990).…”
Section: Discussionmentioning
confidence: 96%
“…lA), suggesting that sulfhydryl oxidation may play a role in heat denaturation in the absence of DTT. The stability of Rubisco is not limited to the spinach enzyme, since high denaturation temperatures were reported for Rubisco from tobacco and alfalfa as well as spinach (Tomimatsu and Donovan, 1981).…”
Section: Discussionmentioning
confidence: 99%